(untitled) (Research, Society and Development, 2022)
This article exposes the importance of inventory management for companies, as well as seeking alternatives to remain in the competitive and increasingly demanding market. The ABC curve is a tool used in numerous companies with an inventory control method that allows managers to have an overview of all products, classifying them based on their monetary value. Thus, this study has the general objective of analyzing the stock management of a paint store. As specific objectives, it seeks to identify the stock management practices used in the studied company; investigate the products with the highest turnover; propose suggestions for improvement in inventory management. The methodology adopted was a survey, the method of applied nature was applied, a quantitative approach with exploratory objectives. As for the results whose proposal is the use of the ABC curve in a paint store, the products with the highest turnover were identified, with a view to reducing costs and maximizing sales, in which the list of products sold and their respective unit values were built, resulting table ABC. This tool made it possible to identify which products should always be available to the customer, as well as those that can be reduced or even eliminated from stock, depending on their turnover. Having identified the products, it was concluded with alternatives that suggest improvements in the practice of stock management in the company, so that the manager identifies the benefits that the tool will bring from its implementation.